Bacillus amyloliquefaciens (IAE635) and their metabolites could purify pollutants, Vibrio spp. and coliform bacteria in coastal aquaculture wastewater - Shao, Yalu; Zhong, Hua; Wang, Liangkai; Elbashier, Mohammed M.A. (International Journal of Agricultural and Biological Engineering, 2021)
High-density aquaculture often causes the emission of polluted water to the marine environment in the coastal areas of China. To solve the aquaculture-related water quality problems, it is appropriate to adapt eco-friendly methods, such as using microbes and their metabolic products to purify polluted water. In this study, the purifying effects of Bacillus amyloliquefaciens (IAE635) metabolites (poly-γ-glutamic acid; PP) and IAE635 combined with their metabolites (MP) on turbidity, COD, NO3–-N, NH4+-N, Vibrio spp. and coliform bacteria in coastal aquaculture wastewater were conducted in the lab and in situ ponds. The results showed that the removal of turbidity, COD, NH4+-N and NO3–-N with PP and MP was more significant (p < 0.05). Compared to Control treatment (Co), the turbidity, COD, NH4+-N and NO3–-N concentrations at 24th hour were evidently reduced by 86.6%, 87.5%, 83.3% and 58.0% for PP, 87.9%, 93.5%, 86.5% and 78.0% for MP, respectively. The populations of water pathogens under PP and MP were also significantly (p < 0.05) removed compared with those of Co; at 24th hour, the Vibrio spp. and coliform bacteria were decreased by 68.7% and 66.3% for PP, 75.0% and 67.1% for MP, respectively. The water purifying effect of MP was slightly better than that of PP. In situ pond purification test demonstrated that MP significantly lowered the concentrations of turbidity, COD, NH4+-N, NO3–-N and NO2–-N, which was more effective than EM. A significantly higher (p < 0.05) γ-PGA concentration and the total bacterial population for MP compared to PP indicated that MP purifies the coastal aquaculture wastewater by both flocculation and microbial decomposition. The application of MP will benefit the aquaculture industry by providing a novel method for the removal of chemical pollutants and pathogens. Keywords: coastal aquaculture, Bacillus amyloliquefaciens and their metabolites (MP), bio-flocculants, chemical pollutants, Vibrio spp., coliform bacteria, wastewater purification DOI: 10.25165/j.ijabe.20211402.6082 Citation: Shao Y L, Zhong H, Wang L K, Elbashier M M A. Bacillus amyloliquefaciens (IAE635) and their metabolites could purify pollutants, Vibrio spp. and coliform bacteria in coastal aquaculture wastewater. Int J Agric & Biol Eng, 2021; 14(2): 205–210.